Enhancing mechanical properties of chitosan/PVA electrospun nanofibers: a comprehensive review - Nur Areisman Mohd Salleh; Amalina Muhammad Afifi; Fathiah Mohamed Zuki; Hanna Sofia SalehHudin (Beilstein Journal of Nanotechnology)
This review examines strategies to enhance the mechanical properties of chitosan/polyvinyl alcohol (PVA) electrospun nanofibers, recognized for their biomedical and industrial applications. It begins by outlining the fundamental properties of chitosan and PVA, highlighting their compatibility and mechanical characteristics. The electrospinning process is discussed, focusing on how various parameters and post-treatment methods influence fiber formation and performance. Key strategies for improvement are analyzed, including material modifications through blending and structural modifications like fiber orientation and multilayer constructions, and surface modifications such as coating and functionalization. The review also covers advanced characterization methods to evaluate mechanical properties and provides a comparative analysis of different enhancement approaches. Applications in biomedical and industrial contexts are explored, showcasing the versatility and innovation potential of these nanofibers. Finally, current challenges are addressed, and future research directions are proposed to overcome these obstacles and further enhance the mechanical properties of chitosan/PVA electrospun nanofibers, guiding their development for practical applications.